2009
DOI: 10.1002/jcp.21882
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HIV‐1 transcription at 3% versus 21% oxygen concentration

Abstract: HIV transcription is induced by the HIV-1 Tat protein, in concert with cellular co-factors including CDK9, CDK2, NF-κB, and others. The cells of most of the body’s organs are exposed to ~3–6% oxygen, but most in vitro studies of HIV replication are conducted at 21% oxygen. We hypothesized that activities of host cell factors involved in HIV-1 replication may differ at 3% versus 21% O2, and that such differences may affect HIV-1 replication. Here we show that Tat-induced HIV-1 transcription was reduced at 3% O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 63 publications
6
31
0
Order By: Relevance
“…We have previously shown that hypoxia decreases the expression of IB-␣ but not that of Gro-␤ or HLA-DRA (48). Data presented in this report suggest that inhibition of CDK9-depedent genes by PPY-based iron chelators could lead to the overexpression of IB-␣ but have no effect on HLA expression.…”
Section: Discussionmentioning
confidence: 57%
“…We have previously shown that hypoxia decreases the expression of IB-␣ but not that of Gro-␤ or HLA-DRA (48). Data presented in this report suggest that inhibition of CDK9-depedent genes by PPY-based iron chelators could lead to the overexpression of IB-␣ but have no effect on HLA expression.…”
Section: Discussionmentioning
confidence: 57%
“…The chelators also signifi cantly reduced association of CDK9 with cyclin T1 and reduced phosphorylation of Ser-2 residues of RNA polymerase II C-terminal domain [ 9 ] , suggesting that the mechanism of inhibition includes deregulation of CDK2 and CDK9. HIV-1 transcription was inhibited in the cells cultured at 3% O 2 compared to 21% O 2 [ 14 ] . At 3% O 2 , the activity of CDK9/cyclin T1 was inhibited and Sp1 activity was reduced, whereas the activity of other host cell factors including CDK2 and NF-κ B was not affected [ 14 ] .…”
Section: Cellular Iron and Hypoxia Infl Uence Hiv-1 Transcriptionmentioning
confidence: 87%
“…HIV-1 transcription was inhibited in the cells cultured at 3% O 2 compared to 21% O 2 [ 14 ] . At 3% O 2 , the activity of CDK9/cyclin T1 was inhibited and Sp1 activity was reduced, whereas the activity of other host cell factors including CDK2 and NF-κ B was not affected [ 14 ] .…”
Section: Cellular Iron and Hypoxia Infl Uence Hiv-1 Transcriptionmentioning
confidence: 87%
See 1 more Smart Citation
“…There is also growing evidence that hypoxia and HIF affect the host-virus interaction and hence the pathogenesis of the viruses that either posses a DNA genome or pass through a DNA stage, contain hypoxia-responsive elements in their promoters, and need the nucleus for their replication. For example, hypoxia enhances gene expression of human B19 erythrovirus (9,29) and replication of oncolytic herpes simplex virus (1) and induces lytic replication of Epstein-Barr virus (18,41) and Kaposi sarcoma-associated herpesvirus (KSHV) (12,15), but it suppresses replication of the oncolytic parvovirus minute virus of mice (35), adenovirus (36), Moloney murine leukemia virus (M-MuLV) (30), and HIV-1 (11,41).…”
mentioning
confidence: 99%